Formación del profesorado desde la investigación y la innovación educativa (EDITUM. Ediciones de la Universidad de Murcia, 2025)
This book contains twenty -two contributions on teacher training in early, primary and secondary education. The areas of knowledge addressed are diverse, specifically seven specific didactics (Spanish, English and French, mathematics, natural sciences, social and plastic sciences), as well as research on educational methodology and attention to diversity.